INDONESIAN AFFIXATION ATTACHED TO ENGLISH WORDS IN ADOLESCENT TABLOID - Dede Jihan Rasika (Journal of Research on Language Education, 2022)
This paper analyzes the pattern of Indonesian affixation which is attached to English words found in 4 famous Adolescent Tabloid namely Keren Beken, Gaul, Fantasi, and Genie. The data were collected by reading the tabloids and taking notes of English words that are being attached by Indonesian affixes. The patterns of those words were analyzed whether or not the affixation changed the word class of English words. From the analyses, it is revealed that Indonesian affixation can be attached to English words. After being attached to English words, Indonesian affixes changed the word class of English words.